Conversion to Islam: A Case Study for the Use of Legal Sources - Simonsohn, Uriel I. (History compass, 2013)
The past few decades have witnessed increasing calls in modern scholarship for revisions of the portrayal of early Islamic rule history. Such calls not only challenge older historiographic paradigms but also encourage historians to seek answers in sources hitherto neglected. Accordingly, in recent years there has been a dramatic proliferation of studies offering new historical conceptions, many of which are indebted to new kinds of source material, including coinage, official documents, inscriptions, and material artifacts, alongside more conventional forms of data like historiographic treatises, biographical dictionaries, apologetic literature, theological essays, and scriptural texts. Assembled together, new and older historical materials were now being processed, synthesized, and analyzed through the lenses of fresh paradigms and often in collaboration with other disciplines, especially the social sciences and comparative literature. The present contribution offers further support of this latter approach by highlighting the utility of legal sources for discussing the process of conversion to Islam in the early Islamic period. Following a brief historical survey, the discussion turns to address one of the central, yet highly elusive, episodes in early Islamic history - the process of conversion to Islam. The goal of this sample analysis of legal sources is twofold - to provide new historiographic insights, but also, from a methodological perspective, to underscore the remarkable utility of these sources for historians.